Worldwide Evaluations of Quinoa—Biodiversity and Food Security under Climate Change Pressures - Pulvento, Cataldo; Bazile, Didier (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This volume collates the main recent developments from studies on quinoa (Chenopodium quinoa Willd.) worldwide. The most important studies focused on the study of the main agronomic practices, ecophysiological traits, genetics, and post-harvest aspects of quinoa. The result of the most recent pieces of research carried out by scientists from international universities and research centers are included.